2023
DOI: 10.3390/biom13020293
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Coloboma Candidate Genes through Conserved Gene Expression Analyses across Four Vertebrate Species

Abstract: Ocular coloboma (OC) is a failure of complete optic fissure closure during embryonic development and presents as a tissue defect along the proximal–distal axis of the ventral eye. It is classed as part of the clinical spectrum of structural eye malformations with microphthalmia and anophthalmia, collectively abbreviated to MAC. Despite deliberate attempts to identify causative variants in MAC, many patients remain without a genetic diagnosis. To reveal potential candidate genes, we utilised transcriptomes expe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…For SNAI2 RNA fluorescence in situ hybridisation we used RNAScope (ACD, Biotechne) following the RNAscope Multiplex Fluorescent V2 Assay protocol on 14 μm cryosections prepared as above and processed as described previously (Hardy et al, 2019;Trejo-Reveles et al, 2023) with the probe ID #1172211-C1. This probe was designed to target Gallus gallus snail family transcriptional repressor 2 (SNAI2) transcript variant X1 mRNA [NCBI GeneID:432368].…”
Section: Fluorescence In Situ Hybridisationmentioning
confidence: 99%
“…For SNAI2 RNA fluorescence in situ hybridisation we used RNAScope (ACD, Biotechne) following the RNAscope Multiplex Fluorescent V2 Assay protocol on 14 μm cryosections prepared as above and processed as described previously (Hardy et al, 2019;Trejo-Reveles et al, 2023) with the probe ID #1172211-C1. This probe was designed to target Gallus gallus snail family transcriptional repressor 2 (SNAI2) transcript variant X1 mRNA [NCBI GeneID:432368].…”
Section: Fluorescence In Situ Hybridisationmentioning
confidence: 99%
“…In addition, translating genetic findings across species is also important in the field of evolution, biology, and genetics. For instance, previous studies demonstrated the conserved functional impacts of orthologous variants on gene expression and complex traits between livestock and humans (23)(24)(25)(26)(27)(28). Liang et al (29) also proposed polygenic transcriptomic risk scores (PTRS), which paved the way to translate polygenic signals across human ancestry groups.…”
Section: Introductionmentioning
confidence: 99%